The Application of Global Method with Picture Word Board Media to Improve The Beginning Reading Skills of Grade I Elementary School Students - Paryati; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2024)
Reading skills are basic skills for students that they must master in order to follow all activities in the education and learning process. Beginning reading is the initial reading given to children in grade I (one). The purpose of this study is to improve the beginning reading skills of grade 1 students as a basis for understanding further lessons. The method used is the PTK model developed by Kurt Lewin. Data analysis techniques are quantitative and qualitative. The obstacles faced include the fact that students' reading skills at the elementary school level tend to be low. This can be seen from the data on student learning outcomes in Indonesian language content in grade 1 SDN 2 Samudra Kulon. It is expected that "Through the Global Method with Picture Word Board Media" can attract students' interest and attention, so that they want to learn with their own desire without feeling forced to do so. This is a great potential to improve beginning reading skills in grade 1 students at SDN 2 Samudra Kulon.